Motif Akun Kuliner Mengikuti Akun Instagram @Sobatjajan.Samarinda - Adissa Cahya Kamila; Kezia Arum Sary; Nurliah Nurliah; Asep Sunandar (SENTRI: Jurnal Riset Ilmiah, 2025)
This study is motivated by the importance of communication effectiveness in the context of food video bloggers (vloggers) on Instagram, which today functions not only as a platform for sharing visually appealing content but also as a medium that can influence followers' preferences and consumption decisions. Food vloggers play a strategic role in shaping consumers' tastes and behaviors, particularly when it comes to choosing dining places and types of cuisine. However, the extent to which these vloggers' communication effectively influences their followers has not been widely studied, especially at the local level, such as in the city of Samarinda. The purpose of this study is to examine how Instagram users in Samarinda process and respond to culinary information delivered by local food accounts. The research employs the Uses and Gratifications theory with a qualitative approach, using observation and interviews with followers of active culinary Instagram accounts. The results show that the majority of followers feel helped by the recommendations provided, particularly in discovering new dining spots and the latest culinary trends. They also perceive these accounts as credible and enjoyable sources of reference for dining choices. This indicates that the communication established by food vloggers is quite effective in influencing their followers' decisions and consumption behavior.